Otomatisasi Sistem Antrean Menggunakan Fast Methodology: Studi Kasus Student Advisory Universitas Bina Nusantara - Heriyanni, Eileen; Gautama, Josef Bernadi; Reina, Reina (ComTech: Computer, Mathematics and Engineering Applications, 2014)
If there is a stack in a service center, then the customers need to form a queue. There are increasing number of consultations in a specific time at Student Advisory Center (SAC) Bina Nusantara University. The increased needs for consultation lead to high waiting time that must be passed by the students who need the service. Therefore an information system queue is required to replace the current manual queue process. This study aims to create an automation using six stages FAST Methodology which includes Scope Definition, Problem Analysis, Requirement Analysis, Logical Design, Decision Analysis, Physical Design and Integration. The results of this research is the design of the application queue screen can be applied to SAC Bina Nusantara University.